King Priam - Macann, Rodney 1950-; Walker, Sarah 1943-; Haskin, Howard 1958-; Mason, Anne 1954-; Price, Janet 1938-; Jenkins, Neil 1945-; Ebrahim, Omar 1956-; Norrington, Roger 1934-; Hytner, Nicholas 1957- (Arthaus Musik, 1985)
Michael Tippett's retelling of the Homeric legend of Troy, centering on the character of King Priam.
Interpr.: Rodney Macann [King Priam], Sarah Walker [Andromache], Howard Haskin [Paris], Anne Mason [Helen], Janet Price [Hecuba], Neil Jenkins [Achilles], Omar Ebrahim [Hector]. Kent Opera Chorus and Orchestra. Conducted by Roger Norrington. Produced by Nicholas Hytner. - Untertitel: engl., dt., franz., span.
Keywords: DVD-Video